Peraturan Presiden No.36 Tahun 2005 dan Berbagai Permasalahannya - Erliyana, Anna (LAW REVIEW, 2005)
Presidential Regulation Number 36 of the year 2005 on Land Availability for Public Usage contains several weakness, such as not taking into considerations what soever that making available of land for public interest must be acquired in fairly manner and, on the first instance, through direct consent by the owner or holder of the ownership right; not mentioning the Law No. 32/2004 on Local Government; Government Regulation No. 40/1996 on The Right of Land of Business, Construction and Private Usage Purposes; Government Regulation No. 24/1997 on Land Registration and Government in the Autonomous Territory; he substantial meaning of public interest has been downsized into, and limited to, the interest of majority of the society, whereas the scope of the projects has been extended; provisions on human rights matter shall be regulated in different laws inform of parliamentary acts.